Economic effect from digital integration: The case of a mechanical engineering enterprise - Andrey S. Vaulin (Journal of New Economy, 2023)
Production digitalisation is a significant factor in the development of mechanical engineering that triggers countries and regions’ economic growth. Implementing digital integration at industrial enterprises implies that production operations are linked through a corporate information system. The paper aims to develop and test a method for assessing the economic effect from digital integration at mechanical engineering enterprises. Methodologically, the study rests on the theories of production organisation and integration as well as the main postulates of the concept of industrial digitalisation. The study applies methods of econometric modelling. The evidence base is the information about the activities of one of the Ural macroregion’s largest mechanical engineering enterprise – Production Association “Ural Optical and Mechanical Plant named after E. S. Yalamov” (UOMZ). The paper systemitises ideas about the essence of the economic effect from digital integration. The case of the enterprise is used to identify the level of specific costs in this process and to forecast their changes depending on different factors using econometric modelling. The value of the findings consists in broadening the scientific and practical understanding of the economic effects brought about by industrial digitalisation.